2008
DOI: 10.1111/j.1537-2995.2008.01694.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of granulocyte–colony‐stimulating factor in volunteer unrelated hemopoietic stem cell donors

Abstract: Granulocyte-colony-stimulating factor (G-CSF) is used for the mobilization of hemopoietic stem cells in healthy donors. It has a number of common side effects such as bone pain, which resolve rapidly after administration is discontinued. Recent publications have raised concern that it might act as a trigger for the development of hematologic malignancy in susceptible individuals, possibly by causing genomic instability, but to date there is no evidence that healthy volunteer donors who receive G-CSF are at any… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
0
37
0
1
Order By: Relevance
“…Thus more data regarding short-and long-term sequels of rhG-CSF administration and leukapheresis have become available. [11][12][13] This study has been the largest prospective series of healthy unrelated donors supervised and followed up by a single apheresis center. The schedules for rhG-CSF administration and leukapheresis were the same in the majority (97.3%) of the donors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus more data regarding short-and long-term sequels of rhG-CSF administration and leukapheresis have become available. [11][12][13] This study has been the largest prospective series of healthy unrelated donors supervised and followed up by a single apheresis center. The schedules for rhG-CSF administration and leukapheresis were the same in the majority (97.3%) of the donors.…”
Section: Discussionmentioning
confidence: 99%
“…12 Until now, there is no convincing evidence that rhG-CSF administration leads to an increased risk to develop hematological malignancies in healthy individuals. 13 The aim of our study was (1) to assess the short-term side effects of rhG-CSF administration and PBPC collection in our sibling donor population by monitoring of medical events and recording laboratory data on days 1, 7, 30 and 100; (2) to evaluate the influence of rhG-CSF and PBPC donation on health status and quality of life (QoL) assessed by a questionnaire in a cross-sectional study and (3) to investigate the long-term safety profile of rhG-CSF by evaluation of retrospective questions on intercurrent events, such as infections, occurrence of new diseases and need for new medications.…”
Section: Introductionmentioning
confidence: 99%
“…The WMDA and several experts in the field produced guidance at that time to indicate that there was insufficient evidence for an increased risk of malignancy in normal donors given G-CSF, and it was not, therefore, recommended to halt the donation of GCSF-mobilized PBSC from UD. [7][8][9][10] Two registry based laboratory studies are currently being performed to investigate these claims further. Thus far the studies have shown no increase in chromosomal abnormalities in PBSC donors compared to bone marrow donors or non-donor healthy controls (D Confer and E Nacheva, personal communications, 2011).…”
mentioning
confidence: 99%